2019
DOI: 10.1186/s13104-019-4078-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral rehydration therapy use and associated factors among under-five children with diarrhea in Dangure, Benishangul Gumuz Region, Ethiopia/2018

Abstract: ObjectivesThis study aims to assess the prevalence of oral rehydration therapy use and associated factors among under-five children with diarrhoea in Dangure district, Benishangul Gumuz Region, Ethiopia/2018.ResultA total of 615 under-five children who suffered from diarrhoea 2 weeks before the study were included and the response rate was 610 (99%). Among the total children participated in this study 189 (31%) were between 12 and 23 months with mean 23.5 and SD ± 6.9. Five hundred seventeen (84.8%) of mothers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
3
16
0
Order By: Relevance
“…11 This could be due to increasing awareness creation on ORT use. This result is in agreement with the study conducted in Dangure, Benishangul Gumuz of Ethiopia 17 and it is lower than the previous study conducted in which 61.8% in Nigeria, 18 61% in Kenya, 19 and 58.2% in Assela Town of Ethiopia. 20 This could be due to socio-demographic differences among study participants, and other health care service-related issues.…”
Section: Discussionsupporting
confidence: 92%
“…11 This could be due to increasing awareness creation on ORT use. This result is in agreement with the study conducted in Dangure, Benishangul Gumuz of Ethiopia 17 and it is lower than the previous study conducted in which 61.8% in Nigeria, 18 61% in Kenya, 19 and 58.2% in Assela Town of Ethiopia. 20 This could be due to socio-demographic differences among study participants, and other health care service-related issues.…”
Section: Discussionsupporting
confidence: 92%
“…The finding is supported by other studies. 15 , 16 , 24 , 27 29 The possible justification might be that educated mothers presume better about the complication of diarrheal disease and they may seek early health treatment during the episode of diarrhea. 30 32 This was a good opportunity for mothers to obtain health education from health professionals and give the appropriate treatment or medication, including ORS, to their sick children.…”
Section: Discussionmentioning
confidence: 99%
“…However, those studies were conducted in specific areas of Ethiopia and were not nationally representative. 15 18 Even there is one study conducted nationally in Ethiopia, which is only focused primarily on individual-level factors 19 without considering the community-level factors. But, ORS utilization can be affected by community-level factors, such as the recommended water source for preparation of ORS, 20 enumeration area (region), distance from health institution, 21 and residence.…”
Section: Introductionmentioning
confidence: 99%
“…However, the ORS coverage for Zimbabwe of 21.0 in the 1st Period was 1.6 to 3.1 times lower than Uganda, Guinea, Ghana, Eritrea, Mozambique, South Africa, Tanzania, Namibia with coverage ranging from 33.5–61.1% [ 20 ]. A 2018 study of Ethiopian mothers reported a prevalence of ORS of 51%, which was lower than the coverage in Zambia and Malawi but higher than the coverage in Zimbabwe [ 21 ]. .In 12 SSA countries not included in our study the median ORS coverage in the 1st Period was lower 38% (35–41) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%